2021
DOI: 10.1101/2021.03.05.434040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective sorting of ancestral introgression in maize and teosinte along an elevational cline

Abstract: While often deleterious, hybridization can also be a key source of genetic variation and pre-adapted haplotypes, enabling rapid evolution and niche expansion. Here we evaluate these opposing selection forces on introgressed ancestry between maize (Zea mays ssp. mays), and its wild teosinte relative. Introgression from ecologically diverse teosinte may have facilitated maize's global range expansion, in particular to challenging high elevation regions (> 1500 m). We generated low-coverage genome sequencing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 126 publications
(160 reference statements)
8
49
0
Order By: Relevance
“…Even after genome-wide admixture proportions have stabilized, theory predicts that minor-parent ancestry will be more fully removed from regions of the genome with low recombination rates ( Wu, 2001 ; Nachman and Payseur, 2012 ). Data from diverse taxa, including swordtail fishes, humans, monkeyflowers, maize, and Heliconius butterflies ( Schumer et al, 2018 ; Calfee, 2021 ; Edelman et al, 2019 ; Brandvain et al, 2014 ; Martin et al, 2019 ), support this theoretical prediction (but see Corbett-Detig and Nielsen, 2017 ). However, differing correlations between recombination rate and gene density can lead to local differences in minor parent ancestry, depending on where in the genome recombination primarily occurs.…”
Section: Emerging Principles Of Hybridizationmentioning
confidence: 93%
See 4 more Smart Citations
“…Even after genome-wide admixture proportions have stabilized, theory predicts that minor-parent ancestry will be more fully removed from regions of the genome with low recombination rates ( Wu, 2001 ; Nachman and Payseur, 2012 ). Data from diverse taxa, including swordtail fishes, humans, monkeyflowers, maize, and Heliconius butterflies ( Schumer et al, 2018 ; Calfee, 2021 ; Edelman et al, 2019 ; Brandvain et al, 2014 ; Martin et al, 2019 ), support this theoretical prediction (but see Corbett-Detig and Nielsen, 2017 ). However, differing correlations between recombination rate and gene density can lead to local differences in minor parent ancestry, depending on where in the genome recombination primarily occurs.…”
Section: Emerging Principles Of Hybridizationmentioning
confidence: 93%
“…Although the sources of selection on hybrids undoubtedly differ between species ( Juric et al, 2016 ; Schumer et al, 2018 ; Brandvain et al, 2014 ), studies across diverse taxa have largely found that regions of the genome that are dense in coding or conserved elements tend to be particularly resistant to movement between species ( Sankararaman et al, 2014 ; Teeter et al, 2008 ; Turissini and Matute, 2017 ; Martin et al, 2013 ; Calfee, 2021 ; Brandvain et al, 2014 ; Masly and Presgraves, 2007 ; Maxwell et al, 2018 ). In the case of conserved regulatory elements in humans, this pattern is stronger at enhancers that harbor derived mutations as opposed to ancestral variants ( Telis et al, 2020 ).…”
Section: Emerging Principles Of Hybridizationmentioning
confidence: 99%
See 3 more Smart Citations